Groupitizing Improves Estimation of Numerosity of Auditory Sequences - Anobile, Giovanni; Castaldi, Elisa; Maldonado Moscoso, Paula A.; Arrighi, Roberto; Burr, David (Frontiers in Human Neuroscience, 2021)
Groupitizing is a recently described phenomenon of numerosity perception where clustering items of a set into smaller “subitizable” groups improves discrimination. Groupitizing is thought to be rooted on the subitizing system, with which it shares several properties: both phenomena accelerate counting and decrease estimation thresholds irrespective of stimulus format (for both simultaneous and sequential numerosity perception) and both rely on attention. As previous research on groupitizing has been almost completely limited to vision, the current study investigates whether it generalizes to other sensory modalities. Participants estimated the numerosity of a series of tones clustered either by proximity in time or by similarity in frequency. We found that compared with unstructured tone sequences, grouping lowered auditory estimation thresholds by up to 20%. The groupitizing advantage was similar across different grouping conditions, temporal proximity and tone frequency similarity. These results mirror the groupitizing effect for visual stimuli, suggesting that, like subitizing, groupitizing is an a-modal phenomenon.